2018
DOI: 10.26656/fr.2017.2(4).070
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional properties of Indian squid (Loligo duvauceli) and cuttlefish (Sepia latimanus) ink powder

Abstract: This study aimed to compare the physical and functional properties of Indian squid (Loligo duvauceli) and cuttlefish (Sepia latimanus) ink powders. Indian squid and cuttlefish are common major sources of seafood products available in Malaysia. However, the inks of these cephalopods are considered waste products. Inks were removed from squids, freezedried, and ground into powder form. The color, pH, water activity, bulk and tapped densities, emulsifying activity and stability, viscosity, water solubility and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The whiteness value of the cuttlefish ink used in this work was 13.98 ± 1.05. These results are similar to those of Ahamed et al (2018) who found that the whiteness value of cuttlefish ink was 14.16. Just after soaking, due to the melanin pigment, a significant difference was observed between the sardine control sample and those soaked with the ink solution (P < 0.05).…”
Section: Whitenesssupporting
confidence: 91%
See 1 more Smart Citation
“…The whiteness value of the cuttlefish ink used in this work was 13.98 ± 1.05. These results are similar to those of Ahamed et al (2018) who found that the whiteness value of cuttlefish ink was 14.16. Just after soaking, due to the melanin pigment, a significant difference was observed between the sardine control sample and those soaked with the ink solution (P < 0.05).…”
Section: Whitenesssupporting
confidence: 91%
“…Cardinal et al (2001) explained this decrease of whiteness by a loss of water in fish muscle. Cuttlefish ink plays a role as a natural food coloring agent (Ahamed et al, 2018). The whiteness value of the cuttlefish ink used in this work was 13.98 ± 1.05.…”
Section: Whitenessmentioning
confidence: 94%